The Influence of Different Factors on Brain Weight - Skukauskaitė, Eglė; Asadauskaitė, Greta; Laima, Sigitas; Chmieliauskas, Sigitas; Stasiūnienė, Jurgita; Vasiljevaitė, Diana; Petreikis, Paulius (Acta medica Lituanica, 2025)
Background: A postmortem brain weight examination can provide valuable diagnostic information on probable causes of death. Deviations from normal brain weight can indicate the presence of different factors such as psychoactive substance use, the presence of neurological conditions, tumours, brain oedema or traumatic brain injury. The aim of this study is to analyse these factors and their role in understanding the underlying causes of death.Materials and methods: This research was designed as a retrospective study. The study sample consisted of 651 autopsy cases from 2013 to 2023. The brain weight was compared between people who died from traumatic brain injury, by hanging, of other sudden causes, and were intoxicated by alcohol or drugs. The collected data were processed by using R software. P values less than 0.05 were considered significant.Results: The mean brain weight of the control group was 1274.93 ± 124.74 g. The mean brain weight of males was greater than that of females. The brain weight was lower in children and the elderly, whereas the greatest in adults between the ages 21–30. In the ethyl alcohol-intoxicated group, the mean brain weight was 1344.01 ± 148.69 g, whereas, in the drug-intoxicated group, it measured 1418.45 ± 125.45 g. The mean brain weight of subjects with strangulation asphyxia was 1372.13 ± 128.83 g, while for those with traumatic brain injury it was 1358.27 ± 150.42 g. The highest brain weight was observed in subjects with epidural hematoma and with subarachnoid haemorrhage. The most frequent complications in patients who died after brain injury were cerebral herniation and pneumonia. The mean brain weight of subjects with cerebral herniation was 1376.95 ± 164.29 g. After traumatic brain injury, skull fractures, brain surgery and cerebral herniation were associated with a higher brain weight. There was a negative correlation between the brain weight and the Glasgow Coma Scale score.Conclusions: A greater brain mass was observed in subjects with ethyl alcohol and drug intoxication, in the groups with strangulation asphyxia and traumatic brain injury compared to the control group. In the traumatic brain injury group, a greater brain weight was observed in men, in those with skull fractures, with epidural haemorrhage, with herniation signs, and after brain surgery.